A Novel Carbazole‐Based Nonfullerene Acceptor for High‐Efficiency Polymer Solar Cells. Issue 3 (7th November 2019) - Ouyang, Jinyang; Zeng, Guang; Xin, Yue; Zhao, Xiaoli; Yang, Xiaoniu
Abstract : It is important to tune the energy levels of nonfullerene acceptors (NFAs) to achieve more balanced open‐circuit voltage ( V oc ) and short‐circuit current density ( J sc ) to improve the device performance. Herein, two novel NFAs are designed via fusing fluorene or carbazole with two thieno[3, 2‐ b ]thiophene and end capped with INIC‐2F, namely, 4TFIC‐4F and 4TCIC‐4F, respectively. The impact of the fluorene and carbazole unit on the PSC performance is systematically studied. Compared with 4TFIC‐4F, 4TCIC‐4F exhibits a higher lowest unoccupied molecular orbital (LUMO) energy level of −3.95 eV and a narrower optical bandgap of 1.51 eV owing to the stronger electron‐donating capacity of fused‐carbazole ring core. Consequently, the 4TCIC‐4F device achieves a high power conversion efficiencies (PCE) of 13.02% with a higher V oc of 0.94 V and a larger J sc of 18.98 mA cm −2, whereas the 4TFIC‐4F device shows a PCE of 11.24%. The PCE of 13.02% is the highest value so far reported with the carbazole‐containing NFAs‐based PSCs. More importantly, the 4TCIC‐4F device shows good film thickness insensitive and long‐term thermal stability. The investigation demonstrates that the fused‐carbazole ring is a superior option to fused‐fluorene ring as electron‐donating core for designing high‐performance NFAs by improving V oc and J sc simultaneously. Abstract : Two novel nonfullerene acceptors (NFAs) 4TFIC‐4F and 4TCIC‐4F are designed based on fluorene and carbazole. Compared with 4TFIC‐4F, 4TCIC‐4F exhibits higher lowest unoccupied molecular orbital (LUMO) level and narrower optical bandgap. Therefore, polymer solar cells based on PBDB‐T‐2Cl:4TCIC‐4F achieve a high‐power conversion efficiency of 13.02%, which is the highest value for the carbazole‐containing NFAs‐based devices.